Ion Mobility Mass Spectrometry of a Rotary ATPase Reveals ATP-induced Reduction in Conformational Flexibility - Zhou, Min (2014)
Rotary ATPases play fundamental roles in energy conversion, their catalytic rotation being associated with inter-domain fluctuations and heterogeneity of conformational states. Using ion mobility mass spectrometry (IM-MS) we compare the conformational dynamics of the intact ATPase from Thermus thermophilus (TtATPase) with its membrane and soluble subcomplexes. Our results define regions with enhanced flexibility assigned to distinct subunits within the overall assembly. To provide a structural context for our experimental data we performed molecular dynamics (MD) simulations and observed conformational changes of the peripheral stalks reflecting their intrinsic flexibility. By isolating complexes at different phases of cell growth and manipulating nucleotides, metal ions and pH during isolation, we reveal differences that can be related to conformational changes in the V(o) complex, triggered by ATP binding. Together these results implicate nucleotides in modulating flexibility of the stator components and uncover mechanistic detail underlying operation and regulation in the context of the holo-enzyme.